Bilous K.S. Problems of establishing and mechanisms for enforcement of political responsibility - Gryshyna, Nataliia (Pressing Problems of Public Administration, 2019)
The article analyzes the problems that hinder the establishment of political responsibility in the public administration of Ukraine. The main mechanisms of ensuring political responsibility are considered.The main directions of their improvement are outlined.